2014
DOI: 10.1177/1363461514526630
|View full text |Cite
|
Sign up to set email alerts
|

Mental and somatic health and pre- and post-migration factors among older Somali refugees in Finland

Abstract: Mental and somatic health was compared between older Somali refugees and their pair-matched Finnish natives, and the role of pre-migration trauma and post-migration stressors among the refugees. One hundred and twenty-eight Somalis between 50-80 years of age were selected from the Somali older adult population living in the Helsinki area (N = 307). Participants were matched with native Finns by gender, age, education, and civic status. The BDI-21 was used for depressive symptoms, the GHQ-12 for psychological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 50 publications
9
63
2
5
Order By: Relevance
“…The two EQ-5D dimensions pain/ discomfort and anxiety/depression were also the two dimensions accounting for the most frequently reported problems among the Swedish general population, which indicates that pain/discomfort and anxiety/depression may act as key drivers of low HRQoL across different non-patient populations. In previous studies from Sweden and Finland, comparing HRQoL between elderly Iranian migrants/Somali refugees and the Swedish/Finnish host population, similar results were found [15,16]. Sex differences in HRQoL were also shown in a study with data from Sweden, where female Iranian migrants had lower scores in all dimensions compared to Swedish women, whereas male Iranian migrants had lower score in six of the eight dimensions measured by SF-36 [16].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The two EQ-5D dimensions pain/ discomfort and anxiety/depression were also the two dimensions accounting for the most frequently reported problems among the Swedish general population, which indicates that pain/discomfort and anxiety/depression may act as key drivers of low HRQoL across different non-patient populations. In previous studies from Sweden and Finland, comparing HRQoL between elderly Iranian migrants/Somali refugees and the Swedish/Finnish host population, similar results were found [15,16]. Sex differences in HRQoL were also shown in a study with data from Sweden, where female Iranian migrants had lower scores in all dimensions compared to Swedish women, whereas male Iranian migrants had lower score in six of the eight dimensions measured by SF-36 [16].…”
Section: Discussionsupporting
confidence: 63%
“…Results from a study in Finland among older Somali refugees showed that they had a lower HRQoL than the matched Finnish host population. Somali refugees reported more on the dimension of anxiety/depression, whereas the Finnish control group reported more on pain/discomfort [15]. The HRQoL in elderly has also been investigated among Iranian refugees resettled in Sweden indicating that Iranian refugees in Sweden reported higher HRQoL than Iranians living in Iran, but lower than native Swedes living in Sweden [16].…”
Section: Introductionmentioning
confidence: 99%
“…Faktoren des Zufluchtslandes sind auf der Makro-(u. a. ökonomische und juristische Bedingungen), der Familien-(u. a. häusliche Gewalt) und der individuellen Ebene (u. a. Inanspruchnahmeverhalten) identifizierbar [20]. Insbesondere wurden Zusammenhänge zwischen niedrigem sozioökonomischem Status [21], unsicheren Arbeitsbe-dingungen und Arbeitslosigkeit [22,23], geringen Kenntnissen der Sprache des Zufluchtslandes [24] sowie Diskriminierung [25,26] und Depression, Angst und PTBS bei Flüchtlingen untersucht (tab. 2 im Internet).…”
Section: Resultsunclassified
“…Entsprechend unserer Einschlusskriterien wurden 15 Studien mit Flüchtlingen aus mehreren Ländern (Bhutan [35], Irak [36][37][38], Kambodscha [39], Kongo [40,41], Liberia [42], Ruanda [43], Somalia [23,44], Syrien [45], Vietnam [46], verschiedene Länder [42,47,48]) mit insgesamt n = 6 769 Flüchtlingen in den Review einbezogen (▶tab. 1).…”
Section: Charakteristika Der Studienunclassified
“…Familial, religious, and ethnic group support has been shown to buffer against poor mental health and enhance wellbeing in African refugees residing in countries of first asylum, as well as those resettled in high-income countries (Abraham et al 2018;Campbell 2006;Gladden 2012;Posselt et al 2018;Schweitzer et al 2006Schweitzer et al , 2007, including in older adult refugees groups (Lamba and Krahn 2003;Silveira and Allebeck 2001;Mölsä et al 2014). Despite these positive findings, there is a knowledge gap related to the specific range and sources of support utilized by refugees across generations in low-and middleincome countries (LMICs), in which 85% of refugees are hosted globally (UNHCR 2018a).…”
Section: Introductionmentioning
confidence: 99%